The Janáček compendium - Simeone, Nigel 1956- (The Boydell Press, 2019)
One of the greatest and most original composers of the early twentieth century, Leos Janacek (1854-1928) occupied a pre-eminent position in Moravian culture, not only as a composer but also as a folksong collector, journalist, educator and nationalist. His friends and associates included artists, writers, ethnographers and politicians, as well as conductors, singers and instrumentalists. Janacek's many pupils included the conductor Bretislav Bakala and the composer Pavel Haas. He had important associations with publishers in Vienna and Prague and with the earliest years of Czech Radio. Janacek was strongly attached to particular places - Hukvaldy, Brno, Luhacovice - and had professional links with Prague, Berlin, London and beyond. The Janacek Compendium includes nearly 300 entries on every aspect of Janacek's life and works, with detailed notes on all his significant compositions - above all the operas - providing the latest information to emerge about some of his most famous pieces. An extensive bibliography supports the entries, which are cross-referenced to enable wider exploration of particular topics. - NIGEL SIMEONE is a widely respected writer and lecturer on music, with a lifelong interest in Czech music. His books include Janacek's Works (Oxford University Press, 1997, co-authored with John Tyrrell and Alena Nemcova), The Leonard Bernstein Letters (Yale University Press, 2013), and Charles Mackerras (Boydell Press, 2015, co-edited with John Tyrrell). He is a regular broadcaster on BBC radio.
Keywords: Janáček, Leoš -- 1854-1928; MUSIC / Genres & Styles / Classical; MUSIC / Reference; Janáček, Leoš / 1854-1928; Biografie; Bibliografie; Werkverzeichnis